FREQUENCY OF COMPLICATIONS OF LAPAROSCOPIC TOTAL EXTRA PERITONEAL INGUINAL HERNIOPLASTY AT MINIMAL INVASIVE SURGICAL CENTRE, JAMSHORO - Mujeeb Rehman Abbasi; Ahmed Khan Sangrasi; Ubedullah Shaikh; A.Razzak Shaikh (Gomal Journal of Medical Sciences, 2016)
Background: There are several different techniques for the treatment of inguinal hernias. The objective of this study was to identify and evaluate the frequency of complications of inguinal hernia repair with a totally extraperitoneal mesh placement. Material & Methods: This descriptive study was done in the Minimal Invasive Surgical Centre, Jamshoro and General Surgical Department, Dow University Hospital, Ojha Campus, Karachi, from January 2014 to December 2014. The sample size was 43. All patients of age >20 years were evaluated, diagnosed with symptomatic inguinal hernia and included in the study. Patient with congenital groin hernia, long standing scrotal hernia, unfit for general anesthesia and previous open surgery for prostate, morbidly obese, elderly patients with co-morbidities complete and complicated hernias were excluded from the present study. The patients were explained the advantages and disadvantages of both the techniques (open and TEP repair techniques). Results: The mean age was 39.3±5.6, ranging between 20 to 60 years. Most of the patients had right sided hernia 28(65.11%) while patients having left sided hernia were 11(25.58%) and patients of bilateral hernia were 4(9.3%). Direct inguinal hernia was mostly observed in old aged patients and they were 19(44.18%) patients while remaining were of indirect hernia 24(55.81%) patients. Intraoperative complications of total extra peritoneal (TEP) inguinal hernioplasty were during port insertion tear, the peritoneum 2(4.6%) cases, bleeding in extra-peritoneal space during dissection 02(4.6%) cases, obscure the anatomy 3(6.9%) cases, inability to reduce the sac completely 4(9.3%) cases, bleeding during separation of sac from cord structures 3(6.9%) cases, femoral nerve injury 1(2.32%) and sub-cutaneous insufflation 1(2.32%) cases. Conclusion: We conclude that laparoscopic hernia repair is one that enables faster time safe, effective recovery and return to productive activity, with a rate of procedural complications TEP is low.